2020
DOI: 10.1016/j.tplants.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Light Emission in Betalains: From Fluorescent Flowers to Biotechnological Applications

Abstract: The discovery of visible fluorescence in the plant pigments betalains revealed the existence of fluorescent patterns in flowers of plants of the order Caryophyllales, where betalains substitute anthocyanins. The serendipitous initial discovery led to a systemized characterization of the role of different substructures on the photophysical phenomenon. Strong fluorescence is general to all members of the family of betaxanthins linked to the structural property that the betalamic acid moiety is connected to an am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 101 publications
0
34
0
1
Order By: Relevance
“…A more pronounced hypsochromic effect is observed in neobetanin (CAS 71199-29-6 = 14,15-dehydrobetanin), which is orange and not violet [ 67 ]. The same effect is found in betaxanthins: a hypsochromic shift occurs upon decarboxylation of portulacaxanthin II (CAS 135545-98-1) and dopaxanthin [ 68 ].…”
Section: Spectroscopic and Fluorescent Properties Of Betalainsmentioning
confidence: 78%
See 1 more Smart Citation
“…A more pronounced hypsochromic effect is observed in neobetanin (CAS 71199-29-6 = 14,15-dehydrobetanin), which is orange and not violet [ 67 ]. The same effect is found in betaxanthins: a hypsochromic shift occurs upon decarboxylation of portulacaxanthin II (CAS 135545-98-1) and dopaxanthin [ 68 ].…”
Section: Spectroscopic and Fluorescent Properties Of Betalainsmentioning
confidence: 78%
“…The existence of intramolecular hydrogen bonds constrains the dynamics of the molecule, favorizing certain structures, as it occurs in miraxanthin I (CAS 5296-79-7). This phenomenon decreases the radiationless energy losses and contributes to the high fluorescence quantum yield of miraxanthin I molecule ( Table S4 ), recognized as the most fluorescent natural betaxanthin [ 68 ].…”
Section: Spectroscopic and Fluorescent Properties Of Betalainsmentioning
confidence: 99%
“…Although betalains have attracted attention in recent years as plant pigments with promising health-promoting potential and visible fluorescence (Gandía-Herrero et al, 2016;Guerrero-Rubio et al, 2020), research on quinoa betalains has only recently begun. A previous mutant analysis indicated that CqCYP76AD1 functions in betalain accumulation during the hypocotyl pigmentation process in quinoa (Imamura et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The relative betacyanin contents were estimated spectrophotometrically based on absorbance at 536 nm (Imamura et al, 2019;Guerrero-Rubio et al, 2020). UV-Vis spectra were acquired using a DeNovix DS-11 (DeNovix, Wilmington DE, United States) spectrophotometer.…”
Section: Pigment Chemical Analysismentioning
confidence: 99%
“…An increased understanding of the betalain biosynthesis pathway has facilitated the metabolic engineering of betalains, providing new sources for basic research studies and commercial applications 22,23 . For example, the uorescent betaxanthins produced by the expression of MjDODAa1 in yeast were used as chemical biosensors to reveal the tyrosine hydroxylase activity of BvCYP76AD1 15 .…”
Section: Introductionmentioning
confidence: 99%